Legal Authority of Sunnah: An Appraisal - Malik, Dr. Zaid Malik (Al Basirah, 2024)
This research is concerned with study of legal authority of Sunnah as the second source of Islamic law. Some scholars have started to spread the notion that Sunnah is not needed in following the teachings of Islam; rather the Holy Qur’an is sufficient for our guidance. The researcher refutes this claim by using the deductive method in his research by reading, analyzing and deriving the subject matter relevant to the topic from the primary sources and mentioning strong arguments from the Holy Qur’an, the traditions of the holy Prophet (ﷺ), sayings of some of his companions and narratives of some early scholars of Islam. Adopting the inductive and deductive methods, the researcher has reached some important conclusions i.e., the need to disclose this claim to the Muslim world, treat it as a conspiracy against Islam, hold a series of seminars and conferences in various parts of the Islamic world to disclose this conspiracy against the Sunnah, reaching a unanimous verdict through consensus (ijma’) among the Muslim scholars of the world on this important issue. This research finds that the Sunnah has been followed by the Muslims long before Imam Bukhari and Imam Muslim. A big part of the Islamic jurisprudence is relying on Sunnah and has been followed by Muslims from the day first till now.